2019
DOI: 10.1109/access.2019.2927552
|View full text |Cite
|
Sign up to set email alerts
|

Malware Classification Using Probability Scoring and Machine Learning

Abstract: Malware classification plays an important role in tracing the attack sources of computer security. However, existing static analysis methods are fast in classification, but they are inefficient in some malware using packing and obfuscation techniques; the dynamic analysis methods have better universality for packing and obfuscation, but they will cause excessive classification cost. To overcome these shortcomings, in this paper, we propose a classification system Malscore based on the probability scoring and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(20 citation statements)
references
References 46 publications
0
20
0
Order By: Relevance
“…In our previous study [7], it has been demonstrated that the opcode sequences captured by variable-length n-grams (n � 2, 3, 4) are more meaningful than fixed-length n-grams.…”
Section: Opcode Sequence Feature Extraction and Selectionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our previous study [7], it has been demonstrated that the opcode sequences captured by variable-length n-grams (n � 2, 3, 4) are more meaningful than fixed-length n-grams.…”
Section: Opcode Sequence Feature Extraction and Selectionmentioning
confidence: 99%
“…So far, malware classification methods mainly focus on feature engineering, which need to extract features from malware or visualization images, for example, API calls [6,7], system calls [8,9], and opcode sequences [10,11]. e malware classification framework in our work is closely related to opcode sequences and SVM.…”
Section: Malware Classificationmentioning
confidence: 99%
“…To overcome the drawbacks of code obfuscation and high computational costs of analysing malware, Xue et al [137] recently proposed Malscore, which is based on the probability scoring and machine learning. The purpose of probability scoring is to decide if static analysis needs to concatenate with dynamic analysis.…”
Section: Neural Network-based Methodsmentioning
confidence: 99%
“…The study utilizes the convolutional neural networks (CNN) for classification and achieved 99.97% and 98.52% accuracy on Microsoft and Malimg datasets, respectively. A malware classification system called 'Malscore' was proposed in [10] which is based on machine learning models and probability scoring. The proposed system works in two phases, where, CNN is utilized with spatial pyramid pooling to examine grayscale images in phase 1, and several n-grams and ML models have been integrated to examine the dynamic features in phase 2.…”
Section: Literature Reviewmentioning
confidence: 99%